(untitled) (Hematology Meeting Reports, 2009)
Chemistry MLN518 (previously CT53518) is a 4-piperaziynylquinazoline derivative. Compounds derived from this pharmacophore were initially developed as inhibitors of the platelet derived growth factor receptors (PDGFR) α and β, tyrosine kinase receptors involved in a number of pathological processes including atherosclerosis, glomerulonephritis and liver cirrhosis. Both receptors additionally play a role in carcinogenesis as a result of constitutive activation by 5’ fusion of domains that lead to dimerization in the absence of ligand or by point mutations.1-3 PDGFR α and β belong to the type III family of receptor tyrosine kinases that is characterized by an extracellular domain containing 5 immunoglobulin-like repeats and a split kinase domain. Other members of this family are Kit, Flt-3 and the colony stimulating factor 1 (CSF-1) receptor. All of these kinases have been implicated in malignancy.